Cluster Analyses Reveals Subgroups of Children With Suspected Auditory Processing Disorders - Sharma, Mridula; Purdy, Suzanne C.; Humburg, Peter (Frontiers in Psychology, 2019)
Background: Some children appear to not hear well in class despite normal hearing sensitivity. These children may be referred for auditory processing disorder (APD) but can also have attention, language, and/or reading disorders. Despite presenting with similar concerns regarding hearing difficulties in difficult listening conditions, the overall profile of deficits can vary in children with suspected or confirmed APD. The current study used cluster analysis to determine whether subprofiles of difficulties could be identified within a cohort of children presenting for auditory processing assessment. Methods: Ninety school-aged children (9-13 years old) with suspected auditory processing disorders were included in a cluster analysis. All children had their reading, language, cognition and auditory processing assessed. Parents also completed the Children’s Auditory Performance Scale. Cluster analysis was based on tasks where age-norms were available, including word reading (Castles and Coltheart irregular and non-words test), phonological awareness (Queensland University Inventory of Literacy), language (Comprehensive Language of Assessment-4, Comprehensive Assessment of Spoken Language), sustained attention, working memory (digits forward and backward), and auditory processing (Frequency Pattern Test, Dichotic Digit Test). Hierarchical cluster analysis was undertaken to determine the optimal number of clusters for the data, followed by a k-means cluster analysis. Results: Hierarchical cluster analysis suggested a four-group solution. The four subgroups can be summarised as follows: children with 1) global deficits, n=35; 2) poor auditory processing with good word reading and phonological awareness skills, n=22; 3) poor auditory processing with poor attention and memory but good language skills, n=15; and 4) poor auditory processing and attention with good memory skills, n=18. Conclusions: The cluster analysis identified distinct subgroups of children. These subgroups display the variation in areas of difficulty observed across different studies in the literature (e.g., not every child with APD has an attention deficit), highlighting the heterogeneous nature of APD and the need to assess a range of skills in children with suspected APD. It would be valuable for future studies to independently verify these subgroups and to determine whether interventions can be optimised based on these subgroups.